2018
DOI: 10.6007/ijarbss/v8-i10/4709
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary Investigation: Accounting Literacy among Small Business Owners

Abstract: Accounting is important for a business of any sizes to keep well-organized and up-to-date accounting records for their daily transactions. It helps businesses to plan and manage financial matters more effectively. However, most of the small business owners do not keep proper books of accounts since there is no legal obligation to do that. Moreover, they also perceive accounting as a very difficult process due to its technical difficulties. Thus, it is quite hard for the small business owners to monitor the fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 11 publications
(9 reference statements)
0
3
0
Order By: Relevance
“…The financial literacy factors influencing variables by Nababan (2012). The indicators accounting literacy used by Roslan. N, et al (2018) to measure accounting variables.…”
Section: Methodsmentioning
confidence: 99%
“…The financial literacy factors influencing variables by Nababan (2012). The indicators accounting literacy used by Roslan. N, et al (2018) to measure accounting variables.…”
Section: Methodsmentioning
confidence: 99%
“…Menurut Trombetta (dalam Nurbaeti et al, 2019) literasi akuntansi sebagai pengetahuan dalam membuat laporan keuangan dalam mengelola bisnis. Literasi akuntansi berupaya membantu seseorang untuk melakukan pencatatan keuangan sehingga diperlukan pengetahuan dan keterampilan oleh akuntan untuk membuat keputusan (Roslan et al, 2018). Selain itu, literasi akuntansi memiliki kaitan teori perilaku terencana sebab dengan sifat logis akuntan dapat memanfaatkan informasi secara sistematis untuk kemudian dilakukan analisis dampak terhadap keputusan yang dilakukan.…”
Section: Hipotesis Literasi Akuntansi Terhadap Komitmen Tidak Korupsiunclassified
“…Literasi akuntansi merupakan kemampuan untuk memahami dan mengelola aspek-aspek keuangan, termasuk pengenalan dan pemahaman mengenai laporan keuangan (Hatta & Budiyati, 2021). Literasi akuntansi berupaya membantu seseorang untuk melakukan pencatatan keuangan sehingga diperlukan pengetahuan dan keterampilan oleh akuntan untuk membuat keputusan (Roslan et al, 2018). Pemerintah berpandangan melalui literasi keuangan, sistem keuangan, kesejahteraan masyarakat, dan pembangunan yang inklusif dapat lebih mudah dicapai.…”
unclassified
“…Muteti et al [41] found that entrepreneurs were noted to keep records in order to remember, observe progress and track profit. Whereas, Germain [42] posited that SMEs perceive record keeping as a method of recovering initial investment in the form of cash at the end of the accounting period. However, if SME's accounting records are not maintained properly, long term sustainability of the business could be affected.…”
Section: The Application Of Accounting Practices Among Microenterprisesmentioning
confidence: 99%